Reversal of Myopic Correction for Patients Intolerant to LASIK - Amr A. Gab-Alla (Journal of Ophthalmology)
Purpose. To evaluate the outcome of the reversal of myopia correction in patients intolerant to LASIK. Methods. This study is a retrospective and case series of patients who decided to reverse their previous myopic LASIK correction between July 2012 and July 2020. It was conducted at a private refractive surgery centre, Ismailia, Egypt. The patients were followed up after reversal treatment for one year. Primary LASIK and reversal treatment were performed by a 500 kHz Amaris excimer laser platform. The main outcomes included refractive predictability, stability, efficacy, and safety and any reported complications. Results. This study included 48 eyes of 24 patients (6 male and 18 female patients). The average duration between the primary LASIK surgery and reversal treatment was 3.20 ± 0.30 months (range 3 to 4 months). Reversal treatment was bilateral in all patients. The mean age of the patients was 38 ± 1.9 years (range 37 to 45 yrs). After reversal, the mean postreversal cycloplegic refraction spherical equivalent was −1.82 ± 0.34 D (range −1.50 to −3.00 D). The mean ablation depth was 34.10 ± 7.36 μm (range 20 to 46 μm), and the mean of the central corneal thickness 12 months after reversal treatment was 510.2 ± 14.4 μm (range 515 to 487 μm). The mean keratometric reading was 42.6 ± 1.6 (range 42.5 to 44.8). The mean of CDVA was 0.2 ± 0.03 log MAR (range −0.10 to 0.4 log MAR). The mean optical zone of reversal treatment was 6.1 ± 0.3 mm (range 5.9 to 6.2 mm). UDVA was 0.4 log MAR in 87.5% of the patients, 0.5 log MAR in 8.3% of the patients, and 0.6 log MAR in 4.2% of the patients. CDVA remained unchanged in 83.3% of patients; 2.1% of the patients gained one line of CDVA (Snellen); 8.3% of the patients lost one line of CDVA; 6.3% of the patients lost two lines of CDVA. No cases of corneal ectasia were recorded. The only postoperative complications were flap microfolds in 3 eyes (6.25%). Conclusion. In conclusion, this study demonstrates that reversal of myopic LASIK treatment is a safe, stable, and effective option for intolerant patients.